The Emergence of Civil Society in Hobbesian Philosophy - Edor John Edor (Jurnal Office, 2020)
The origin of the modern state has left many scholars intellectually engaged. Sociologists, psychologists, political scientists, jurists, anthropologists, and philosophers have variously grappled with the issue of the origin of the state. Thomas Hobbes is one of the great thinkers who has contributed to the discussion on the origin of the state. Thomas Hobbes is of the view that naturally, that is, man in the state of nature, is a-social, atavistically thinking about himself alone. Because of this atomistic and solitary disposition of man in the state of nature, the society was accentuated by an unprecedented degree of rancor, acrimony and obfuscation. Given this picture of man and the pre-civil-society depicted by Hobbes, one would feel that justifying the emergence of the civil society would become difficult. This paper examines how Hobbes migrated man from the state of nature to the civil society in spite of the gory picture of him he had painted. Thomas Hobbes’ theory of the origin of the state is categorized in the class of the social contract theories.